Novel KMT2B mutation causes cerebellar ataxia: Expanding the clinical phenotype. Issue 6 (8th September 2021) - Damásio, Joana; Santos, Mariana; Samões, Raquel; Araújo, Maria; Macedo, Mafalda; Sardoeira, Ana; Cavaco, Sara; Freitas, Joel; Barros, José; Oliveira, Jorge; Sequeiros, Jorge
Abstract: Hereditary cerebellar ataxias comprise a heterogeneous group of neurodegenerative disorders affecting the cerebellum and/or cerebellar pathways. Next‐generation sequencing techniques have contributed substantially to the expansion of ataxia‐causing genes, including genes classically described in alternative phenotypes. Herein, we describe a patient with adult‐onset cerebellar ataxia, minor dystonia, neuropathy, seizure and ophthalmological pathology, who bears a novel variant in KMT2B (NM_014727.2:c.3334 + 1G > A). Bioinformatic analysis suggested this variant completely abolished the splice‐site at exon 8/intron 8, which was confirmed through analysis of mRNA extracted from fibroblasts. Exon 8 skipping would ultimately translate as an in‐frame deletion at the protein level, corresponding to the loss of 91 aminoacids [p.(Gly1020_Asn1111del)]. So far, KMT2B disease causing variants have been described in patients with dystonia or neurodevelopmental delay, with no reports of a cerebellar predominant phenotype. Our findings highlight the possible role of KMT2B as a gene involved in hereditary cerebellar ataxias. Abstract : Damásio et al report for the first time a cerebellar dominant phenotype within KMT2B related disorders, further expanding the phenotypic spectra associated with this gene. On brain MRIs it is documented progressive cerebellar and brainstem atrophy. A novel pathogenic variant on KMT2B is described, and mRNA studies provided to confirm its effect on splicing.